Evaluation of Usefulness of Latex Agglutination Test in Cerebrospinal Fluid for Diagnosis of Acute Bacterial Meningitis (Journal of Chittagong Medical College Teachers' Association, 2023)
Background: Early definite diagnosis and appropriate treatment is the cornerstone for reducing mortality and morbidity in Acute Bacterial Meningitis (ABM). In recent years, there has been considerable interest in rapid antigen detection tests that provide fast species identification. This study aimed to evaluate the usefulness of the Latex Agglutination Test (LAT) for diagnosing ABM.Materials and methods: This cross-sectional study was carried out in the Department of Neurology, Medicine, and Pediatric of Chittagong Medical College Hospital. A total of 68 clinically suspected ABM cases of different ages were included in that study. Specimens of Cerebrospinal Fluid (CSF) were tested for routine CSF study including Gram stain with microscopy, LAT and culture. The entire group under the study got different antibiotics for a period of 24 to 72 hours before CSF sample was collected.Results: Using LAT, an etiological diagnosis was achieved in 22 (32.4%) out of 68 cases of suspected ABM. In contrast, Gram stain and culture showed 23% and 7% positivity, respectively. Streptococcus pneumoniae was the most common causative pathogen as 17 of the cases were found to have this organism. This was followed by 2 cases of Haemophilus influenzae, 2 cases Neisseria meningitidis and 1 case of Group b streptococcus. Conclusion: LAT seems to be a useful and efficient method, at least in parallel to CSF culture and Gram stain to detect the pathogens that are known to be the common cause of ABM. It can be added as an adjunct laboratory test for early diagnosis of ABM especially in pretreated cases for prompt initiation of proper antibiotics. Nevertheless, findings of the present study suggest further large-scale studies in order to confirm its usefulness.JCMCTA 2023 ; 34 (1) : 15-20